1997
DOI: 10.1002/(sici)1097-4598(199704)20:4<479::aid-mus11>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Muscle hypertrophy in multifocal motor neuropathy is associated with continuous motor unit activity

Abstract: Multifocal motor neuropathy (MMN) is typically associated with distal upper limb weakness and wasting. However, proximal muscle bulk, particularly of biceps brachii, may be well preserved even in the presence of severe proximal weakness. Here we report 3 patients with MMN who had true muscle hypertrophy of severely weakened biceps muscles and positive motor symptoms including cramp and fasciculations in these muscles. Electromyographic studies demonstrated markedly impaired recruitment in the affected muscles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
1
15
0
2
Order By: Relevance
“…Two retrospective studies on the natural course of MMN have been published; both reported a slowly progressive course. 22,32 Step-wise 31,55 and spontaneously remitting 2,19 disease courses have also been described but are less common than the slow progressive course. In a study of 38 patients with MMN, we 32 showed that disease duration and disease severity are related.…”
Section: Natural Coursementioning
confidence: 99%
“…Two retrospective studies on the natural course of MMN have been published; both reported a slowly progressive course. 22,32 Step-wise 31,55 and spontaneously remitting 2,19 disease courses have also been described but are less common than the slow progressive course. In a study of 38 patients with MMN, we 32 showed that disease duration and disease severity are related.…”
Section: Natural Coursementioning
confidence: 99%
“…Localized muscle hypertrophy can be because of increased mechanical stimulus [6,10] but occurs also in nerve, muscle, or skeletal disorders with nerve compression and denervation, e.g. axonal neuropathy, discopathy [19], cervical spondylosis, radiculopathies [11], and in various myopathies [3,20] and neuropathies [8,12,21]. Further underlying causes can be adolescence or medication with testosterone, anabolic steroids, or growth hormones.…”
Section: Discussionmentioning
confidence: 99%
“…A number of neuromuscular disorders can cause muscle hypertrophy [17] or hyperplasia [15]. Laboratory tests accompanied by ultrasound [17], magnetic resonance imaging (MRI) [1,14] and neurophysiologic analyses [12], supplemented by histopathology [20], are used in concert to find the correct diagnosis. Idiopathic hypertrophy of hand muscles is rare.…”
Section: Introductionmentioning
confidence: 99%
“…Neuralgic muscle hypertrophy of the limbs has been reported in several types of lower motor neuron disease, such as multifocal motor neuropathy [1], Guillain-Barré syndrome [1], and radiculopathy [3,4], but such hypertrophy involving cranial nerves has not been reported previously to our knowledge. Prior studies suggest that continuous, spontaneous electrical activity of a muscle associated with disease conditions can cause neuralgic hypertrophy [1][2][3][4][5].…”
Section: Dear Sirsmentioning
confidence: 99%